Morphological characterization and selection for high yielding and powdery mildew resistant pea (Pisum sativum) lines - Iqbal, Ajmal; Shah, Shahen; Nisar, Mohammad; Ghafoor, Abdul (Penerbit Universiti Kebangsaan Malaysia, 2017)
Twenty lines of Pisum sativum particularly developed for high yield and resistant to powdery mildew were evaluated along with two parents (Falloner and 11760-3ER) and two checks (Climex and a local cultivar) with the objectives to determine morphological characterization, yield potential and resistance to powdery mildew. On the basis of one way cluster, the 24 lines were mainly grouped into four clusters, especially on the vegetative and yield contributing traits. It was observed that the tall and high yielding lines were grouped in cluster-III while the dwarf and high yielding lines were grouped in cluster-IV. Analysis of variance (ANOVA) showed significant difference (p<0.05) in the yield of 24 pea lines. The average grain yield of the 24 pea lines ranged from 22.87 to 102.54 g. The highest grain yield was produced by PL-4 (102.54 g plant-1) followed by PL-5 (82.14 g plant-1). Of the 24 pea lines, two lines (PL-4 and PL-5) were highly resistant to powdery mildew disease. Therefore, the newly developed PL-4 and PL-5 lines were high yielding and highly resistant. Among the 19 morphological traits, six (Eigenvalue >1.0) contributed more than 80% variability among the materials.